ChemInform Abstract: Total Synthesis of Natural Dihydropyranones: A Contribution to the Structural Elucidation of Natural Products. Coibacins A and B, Cryptomoscatones D1, D2 and E3. Issue 17 (April 2016) - Pilli, Ronaldo Aloise; Toneto Novaes, Luiz Fernando; Teixeira Carneiro, Vania Maria; Drekener, Roberta Lopes; Avila, Carolina Martins
Abstract: Review: 37 refs.